2017
DOI: 10.1002/bit.26511
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 association with mAbs: Mechanism and potential mitigation strategies

Abstract: Process control for manufacturing biologics is critical for ensuring product quality, safety, and lot to lot consistency of therapeutic proteins. In this study, we investigated the root cause of the pink coloration observed for various in-process pools and drug substances in the antibody manufacturing process. Vitamin B is covalently bound to mAbs via a cobalt-sulfur coordinate bond via the cysteine residues. The vitamin B was identified to attach to an IgG4 molecule at cysteine residues on light chain (Cys-21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Although there are many suggested additives that can stabilize cyanocobalamin, (see Macek, ; Kirschbaum, for comprehensive lists), the most recognized are ferric salts (e.g., FeCl 3 and saccharated iron oxide) (Macek, ; Newmark, ; Skeggs, ), phosphate buffer (Monajjemzadeh et al, ), and potassium ferrocyanide (Zuck & Conine, ). A considerably novel method for minimizing the cyano‐to‐hydroxocobalamin conversion is the application of red light filters in the working laboratory, to filter out the lower wavelengths of light (<600 nm) that contribute most to this reaction (Du et al, ). This was shown to be especially relevant to the biomanufacturing industry as it was demonstrated that the B 12 cobalamins can be incorporated into therapeutic mAbs as a result of thiolates in the protein reacting with hydroxocobalamin, forming a sulfide‐cobalt linkage, which is analogous to in vivo ligand‐exchange processes.…”
Section: Cyanocobalaminmentioning
confidence: 99%
“…Although there are many suggested additives that can stabilize cyanocobalamin, (see Macek, ; Kirschbaum, for comprehensive lists), the most recognized are ferric salts (e.g., FeCl 3 and saccharated iron oxide) (Macek, ; Newmark, ; Skeggs, ), phosphate buffer (Monajjemzadeh et al, ), and potassium ferrocyanide (Zuck & Conine, ). A considerably novel method for minimizing the cyano‐to‐hydroxocobalamin conversion is the application of red light filters in the working laboratory, to filter out the lower wavelengths of light (<600 nm) that contribute most to this reaction (Du et al, ). This was shown to be especially relevant to the biomanufacturing industry as it was demonstrated that the B 12 cobalamins can be incorporated into therapeutic mAbs as a result of thiolates in the protein reacting with hydroxocobalamin, forming a sulfide‐cobalt linkage, which is analogous to in vivo ligand‐exchange processes.…”
Section: Cyanocobalaminmentioning
confidence: 99%
“…Association of vitamin B12, in its hydroxocobalamin form has been reported in a number of instances to contribute to a red/pink coloration of mAbs of different isotypes and Fc-Fusion purified material [8,[10][11][12]. Red colored mAbs were found to have absorbance at about 365 nm, which corresponds to one of the absorbance maximum of vitamin B12 (Table 2, Figure 6).…”
Section: Formation Of Extrinsic Chromophores Originating From Cell Culture Componentsmentioning
confidence: 90%
“…12,16 More recently, covalent modification of photoexposed recombinant antibodies in the presence of cyanocobalamin (vitamin B12) in culture media has been observed. 17 While the exposure resulted in a pink coloration of process intermediates and final drug substance, no impact to binding or potency was reported. Product quality attributes that impact potency will have a direct influence on clinical performance of the drug product, elevating the need for effective process control and monitoring strategies during development.…”
Section: Introductionmentioning
confidence: 99%